Exploring stories of trust from foster youth in college - DeLuca, Anne (Kansas State University, 2023)
This narrative study explores the experiences of five college students who were formerly involved with foster care. This study explores the ways former foster youth students tell stories of trust built or trust broken with adults before and during college. The data analysis revealed themes that add to the body of research by providing a clearer understanding of the experiences students share about trust-building or distrust throughout childhood and college. Themes identified before college include: covering up home life during childhood, distrust in biological family, shifting trust to an adult outside of the family, and a revolving door of adults as a barrier to trust building. Themes identified during college include: trusting professors, building boundaries with others, and ongoing management of family status. Finally, participants shared living between trust in self and needing reassurance throughout college. By contributing to the current literature, higher education professionals are encouraged to use these findings to advocate for full-time staff and nuanced programming for foster youth. University leaders are encouraged to use these findings to ensure the needed supports are in place for each student.
Keywords: Foster youth; Retention; Trust; Narrative study